Frontline employee anger in response to customer incivility: Antecedents and consequences. (July 2021) - Li, Shanshi; Zhan, Jueying; Cheng, Bao; Scott, Noel
Abstract: This study examines the antecedents and consequences of frontline employee (FLE) anger evoked by customer incivility as well as the moderating effect of emotion regulation. The cognitive appraisal theory provides the theoretical basis for this study. Data were collected from a sample of 296 frontline service employees in four hotels in Guangzhou City, China. The results demonstrate that, while goal incongruence, goal importance, and other-agency positively predicted anger, coping potential negatively influenced anger. Furthermore, the effects of cognitive appraisals on FLE retaliation intention were mediated by anger. Additionally, FLE emotion regulation ability significantly moderated the relationship between anger and retaliation intention. Our findings extend the literature on customer incivility by demonstrating the psychological mechanism underlying how customer incivility triggers FLE retaliation intention. Highlights: This study investigates the mechanism of how customer incivility incidents lead to retaliation intention. Goal incongruence/importance, and other-agency positively predicted anger, and coping potential negatively influenced anger. The effects of cognitive appraisals on FLE retaliation intention was mediated by anger. ERA acted as a moderating factor and weakened the relationship between anger and retaliation intention.